THE EFFECT GROUP INVESTIGATION METHOD ON LANGUAGE LEARNING OUTCOMES - Ahmad Amarullah; Enawar Enawar (University of Kuningan, 2021)
The purpose of this study was to determine the effect of using group investigation method on second language learning outcomes (L2) in third grade students of SD Muhammadiyah 4 Tangerang City. The method used in this study was a quasi-experimental method by conducting pretest and posttest in two groups. This type of experimental research method uses a nonequivalent control group design, where the experimental class is treated and the control class is not treated. This nonequivalent control group design is almost the same as the pretest and posttest control group designs, only in this design the experimental and control groups are not chosen randomly. Data collection techniques using tests. The data analysis technique was started from normality test, homogeneity test, and continued with hypothesis testing. research data, calculations to test the hypothesis can be that t count is 13.31 and t table with dk = 58. Therefore, the price of t count 13.31 > 1.67 = t table means the null hypothesis (H0) is rejected and the hypothesis alternative (H1) is accepted. Based on the research above, it can be concluded that: there is a significant effect on the second language learning outcomes (L2) of students who use cooperative learning group investigation type compared to conventional methods. Second language learning outcomes (L2) of students who use cooperative learning group investigation type are higher compared to the conventional method, it can be said that the cooperative learning type group investigation method has an effect on students' second language (L2) learning outcomes.